(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2019)
The aim of this work is to reconstruct the linguisitic and cultural view of a Pole from our neighbours’ perspective, including Russians, Lithuanians, Belorussians, Ukrainians, Slovaks, Czechs, and Germans. The primary research method used in this work was the linquistic world’s view method by Jerzy Bartmiński, and the concept of a stereotype as a stabilised view of someone or somethingAn important goal of my study was to compare my survey results with the results of previous research done on the image of a Pole, with the use of various methods, such as sociological, ethnolinguistic and ethnocultural. The comperative approach to the data collected by other researchers allowed to indicate the similarities and differences which emerged in the perception of a Pole for the neighbours’ perspective in over 20 years, as well as to consider the impact of current affairs on enchancing the national stereotype capacity.